The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/nu14010230
|View full text |Cite
|
Sign up to set email alerts
|

Labelling Assessment of Greek “Quality Label” Prepacked Cheeses as the Basis for a Branded Food Composition Database

Abstract: A labelling assessment study of Greek prepacked “quality label” cheeses was conducted with a view to provide an overview of the whole category. In total, 158 prepacked products belonging to 19 “quality label” cheeses were identified in the Greek market. Among them, Feta had the highest share followed by Kasseri, Graviera Kritis, Kefalograviera and Ladotyri Mitilinis with 81, 16, 15, 11 and 9 products found in the market, respectively. For the rest of the 14 cheeses, the share was limited, ranging from 1 to 4. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…In Greece, twenty-two cheeses are registered as protected designation of origin (PDO) and one as a protected geographical indication (PGI). Their characteristics have recently been studied [4][5][6], and their quantities [7] are presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Greece, twenty-two cheeses are registered as protected designation of origin (PDO) and one as a protected geographical indication (PGI). Their characteristics have recently been studied [4][5][6], and their quantities [7] are presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Dairy 2023, 4 Their characteristics may vary due to many factors, such as environmental and specific production conditions, a lack of a standardized production process, etc. [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have been conducted to determine the impacts of disclosing menu item nutrition information on customers’ product assessments, purchase intentions and behaviour [ 7 , 8 ]. A recent study conducted by Aitken et al [ 9 ] on the benefits of menu labelling of organic foods suggested improving labelling to have more actionable information, such as the health, environmental and societal benefits of products.…”
Section: Introductionmentioning
confidence: 99%
“…The same generic fermented food can have many unique formulations depending on the manufacturing source. Here, the use of branded food databases (where information on food composition is provided by manufacturers, food monitoring, and crowdsourcing) are gaining momentum and could be a valuable resource in comprehensively capturing the ingredients within branded fermented foods (106)(107)(108). Documenting the composition of fermented foods could open new research avenues for understanding how their consumption affects health and disease.…”
Section: Better Understanding the Composition Of Different Fermented ...mentioning
confidence: 99%